Can â€œGoyang Karawangâ€ Be a Brand of Karawang Tourism City? - Sumarni, Neni; Suherman, Enjang; Nurlenawati, Netti; Nasihin, Ihsan (Almana : Jurnal Manajemen dan Bisnis, 2025)
Goyang Karawang is one of the nicknames given to the city of Karawang, apart from "Granary Rice", and "Industrial City" Can "Goyang Karawang" be used as a brand for the Karawang Tourism City? The purpose of this study was to determine and analyze whether "Goyang Karawang" can be used as a brand of Karawang tourist city. The research method used a qualitative single case study method, namely; collecting, presenting, analyzing, triangulating, and testing validity and making conclusions and suggestions. Data analysis in the field used the Milles and Hubberman model, with the number of informants consisting of 6 internal informants and 10 external informants taken randomly from Karawang tourist visitors. The results of the study showed that "Goyang Karawang" is not a brand of Karawang tourist city but only a nickname attached to Karawang due to cultural factors, traditions, and customs of a region that always presents the charm of jaipong as a dance art in Karawang. "Goyang Karawang" cannot be used as a brand of Karawang tourist city because it does not reflect the elements of tourism in Karawang. Goyang Karawang as one of the identities of jaipong dance culture is expected to be one of Karawang's tourist attractions.